Human trafficking - Haerens, Margaret (Global viewpoints, 2012)
The Global Viewpoints series provides students and other readers with the information they need to explore global connections and think critically about the worldwide implications of global issues. Each volume focuses on a controversial topic of worldwide importance and offers a panoramic view of opinions selected from a diverse range of international sources, including journals, magazines, newspapers, nonfiction books, speeches, government documents, organization newsletters, and position papers. Each volume contains an annotated table of contents, a world map, to help readers locate countries or areas covered in the essarys, "for further discussion" questions, a worldwide list of organizations to contact; bibliographies of books and periodicals; and a subject index. By illuminating the complexities and interrelations of the global community, this excellent resource helps students and other researchers enhance their global awareness